(untitled) (Fiep Bulletin - online, 2012)
This workrefers toastampbibliographicresearchandbackground inthe field withrenowned authorswithHuizinga(2000), Freire(2005)among others whohold forthon thattheme: fun and games, which emerged fromareflection on practicethese activitiesin the municipality ofAltamira/PA, as well as its contribution to thepsychosocial developmentof the individual, as are characteristic elementsof human life.The aimof thisstudy was torecall thefun and gamespracticedby the elderlyin its infancyand establishacomparison betweenthose practicedbytoday’s youthin the municipality ofAltamira/ PA.Afterthesystematicstudy concludesthatchildren andseniorssurveyedhave playedor madeany toys, among the most varied, ranging fromcars, dolls cornupsoccer balls andrecallthat whenthey missthistime inrelation topopular activitiesthat markedhis lifestand outrhymesfor the elderlyandchophides orconcealsfor children /adolescents.